Potential for Chemical Repellents Against the Mite Tyrophagus putrescentiae to Prevent Infestation of Country Hams - Ciesielski, Cadence; Manu, Naomi; Phillips, Thomas (My University, 2018)
Tyrophagus putrescentiae (Shrank), commonly known as the ham mite, is a cosmopolitan pest found of various stored food commodities, including aged hams and cheeses (Amoah et al. 2017; Campbell et al. 2017). Recent research suggested methods to deter T. putrescentiae from infestation of country hams using different types of food-safe chemicals (Abbar et al. 2016). In this experiment, four chemicals were tested to ascertain their effectiveness in deterring T. putrescentiae from ham infestation. Repellency tests used a piece of ham and a group of mites placed on opposite sides of a Petri dish with a black construction paper floor. A test barrier of a test compound or solvent control was deposited on a white filter paper strip bisecting the dish at its center. The chemicals Nootkatone, Propylene Glycol, Glycerol and a fatty acid blend called “C8910” prevented more mites from contacting the ham compared to strips with solvent. These results suggest the potential for using one or more of these food-safe compounds to prevent ham mites form infesting hams in aging rooms.
Keywords: Fall 2018